Sequential spectrophotometric determination of chromium(III) and chromium(VI) using flow injection analysis - De Andrade, João Carlos; Rochat, Julio Cesar [UNESP]; Baccan, Nivaldo (Royal Society of Chemistry (RSC), 1985)
A flow injection analysis (FIA) procedure for the speciation of Cr(III) and Cr(VI) using the 1,5-diphenylcarbazide (DPC) method is presented. As Cr(III) does not interfere in the Cr(VI) - DPC reaction, both Cr(VI) and total chromium [after the on-line oxidation of Cr(III) by Ce(IV)] are sequentially determined. Cr(III) is obtained by difference. Under the experimental conditions described, the calibration graphs are linear up to 2 μg mh1 of Cr(VI) and 4 μg ml-1 of Cr(III). The detection limits found were 18 ng ml -1 for Cr(VI) and 55 ng ml-1 for Cr(III), at a signal to noise ratio of 3. The common interfering elements in the Cr(VI) - DPC reaction were investigated under dynamic FIA conditions. The FIA method was also compared with the conventional spectrophotometric procedure.
Keywords: Chromium determination; Chromium speciation; Flow injection analysis; Spectrophotometry